Konstruktionssemantik Frames in gebrauchsbasierter Konstruktionsgrammatik und Konstruktikographie - Willich, Alexander (Linguistik - Impulse & Tendenzen, 2022)
Construction semantics combines usage-based construction grammar and frame semantics, as set out in the FrameNet project. This volume models the semantic properties of grammatical constructions and their instances by utilizing frames. It demonstrates the usability of this approach for the constructicographical documentation of constructions as well as its empirical application by looking at three German reflexive constructions.